IL-17A Neutralization Improves the Neurological Outcome of Mice With Ischemic Stroke and Inhibits Caspase-12-Dependent Apoptosis - Dai, Qingqing; Han, Song; Liu, Ting; Zheng, Jiayin; Liu, Cui; Li, Junfa; Li, Shujuan (Frontiers in Aging Neuroscience, 2020)
We previously reported that the levels of astrocyte-derived interleukin (IL)-17A increased both in the peri-infarct region and cerebral spinal fluid (CSF) of mice with 1 h middle cerebral artery occlusion/12 h reperfusion (1 h MCAO/R 12 h)-induced ischemic stroke. However, the effect of IL-17A neutralization on the neurological outcome of mice with ischemic stroke and its underlying molecular mechanism are unclear. In this study, we found that the intracerebroventricular injection of IL-17A neutralizing monoclonal antibody (2.0 µg) could reduce the infarct volume, alleviate neuron loss and improve the neurological outcomes of mice with 1 h MCAO/R 24 h or 3 d-induced ischemic stroked mice. The IL-17A neutralization could also significantly inhibit the increase of pro-caspase-3 cleavage through Caspase-12-dependent cell apoptosis, as well as preventing the decrease of anti-apoptotic factor B-cell lymphoma 2 (Bcl-2) and the increase of pro-apoptotic Bcl-2 associated X protein (Bax) in the peri-infarct region of mice following ischemic stroke. In addition, we confirmed that the recombinant mouse (rm)IL-17A could significantly aggravate 1 h oxygen-glucose deprivation/24 h reoxygenation (1 h OGD/R 24 h)-induced ischemic injuries in cortical neurons at dose-dependent manner; and the rmIL-17A could also exacerbate neuronal apoptosis through Caspase-12 (not caspase-8 or -9)-dependent pathway. These results suggested that IL-17A neutralization could improves the neurological outcome of mice with ischemic stroke through inhibiting Caspase-12 dependent neuronal apoptosis.